(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This research article explores the intricate relationship between food security and the Sustainable Development Goals (SDGs), with a specific focus on India’s efforts to attain SDG 2, "Zero Hunger." Food security is not only a fundamental human right but also a critical component of sustainable development. India, as one of the world’s most populous and diverse nations, plays a significant role in shaping global progress toward achieving the SDGs. This study examines India’s progress towards SDG 2 and investigates its impact on other interconnected SDGs, emphasizing the complex web of interdependencies that exists within the framework of sustainable development. By delving into the multifaceted dimensions of food security, from agricultural production and distribution to nutritional outcomes and social inclusivity, this research endeavors to provide a nuanced perspective on India’s progress.